MECHANICAL BEHAVIOR OF CRUSHED ROCK BASE (CRB) UNDER REPEATED LOADS - K. Siripun; P. Jitsangiam; H. Nikraz (International Association of Lowland Technology, 2010)
This paper aims to report the mechanical behavior of a crushed rock base (CRB) subjected to repeated loads from Repeated Loads Triaxial (RLT) test with various stress paths in order to improve more understanding of roads based materials on mechanistic-empirical pavement design and analysis. As is well known, pavement suface rutiing, longitudinal and alligator cracks are normally the main cause of damage in flexible pavements. Factors contributing to such damage are the excessive irreversible and reversible deformation of a base layer including the behavior of a mechanical response of CRB under traffic load is not well understood. In this study, the shakedown concept was utilized to describe and determine limited use of CRB subjected to different stress condition defined by the stress ratio (the ratio of vertical major stress, σ1 and a horizontal minor stress, σ3) in order to simulate the real condition of pavement. The study reports that CRB was defined the working stress ratio of 11 in pavement structure and will show rutting deterioration at the large number of load cycles after a stable state. Moreover, the mechanical responses were investigated and limit ranges of using CRB in pavements were determined.